The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.2147/jpr.s137609
|View full text |Cite
|
Sign up to set email alerts
|

Improved health-related quality of life, participation, and autonomy in patients with treatment-resistant chronic pain after an intensive social cognitive intervention with the participation of support partners

Abstract: Despite the availability of various specific treatments, most patients with chronic pain (CP) consider their pain problem as undertreated. Recently, multiple sclerosis (MS) patients who were given an intensive 3-day social cognitive treatment with the participation of support partners experienced lasting improvements in health-related quality of life (HRQoL) and self-efficacy. In this study, a similar intervention was given to treatment-resistant CP patients with stressors, relational problems with support par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…An unmasked RCT assessed the effect of CDT, an intensive 3-day multidisciplinary social cognitive theory-based treatment, on control self-efficacy in low-disability RRMS patients and found no difference compared with waitlist controls who had the option to receive the intervention after study participation.We think that the CDT concept may be further developed, e.g. by selecting patients with evident points of interaction, such as stressors, high levels of distress or relational problems with (support) partner [24], and by applying out-patients settings or web-based applications.…”
Section: Discussionmentioning
confidence: 99%
“…An unmasked RCT assessed the effect of CDT, an intensive 3-day multidisciplinary social cognitive theory-based treatment, on control self-efficacy in low-disability RRMS patients and found no difference compared with waitlist controls who had the option to receive the intervention after study participation.We think that the CDT concept may be further developed, e.g. by selecting patients with evident points of interaction, such as stressors, high levels of distress or relational problems with (support) partner [24], and by applying out-patients settings or web-based applications.…”
Section: Discussionmentioning
confidence: 99%
“…This study was permitted to use the EQ-5D-5L questionnaires by the EuroQol Research Foundation (ID Number 28208). The EQ-5D-5L defines health in terms of five dimensions: 1) mobility, 2) self-care, 3) usual activities, 4) pain/discomfort and 5) anxiety/depression [ 15 , 16 ]. Each dimension has five levels including extreme, severe, moderate, slight and no problem [ 15 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…in one observational study, a similar intervention was successful in patients with intractable chronic pain 32 . In addition, the effects of CDT may be expected to be generalizable to other (western) societies, as is suggested in the study by Ng et al 57 on a similar intervention in American patients with MS. 7.…”
Section: Practical Implications Of the Study Findings And Current Knomentioning
confidence: 97%
“…In the first two SUAs [SUA1 and SUA2] only patients showing a clinically meaningful increase in MSSES Control at 6 months were selected (75 or more points); in two other SUAs [SUA3 and SUA4], the 50% of the patients with the lowest MSSES Control scores at baseline were selected. The selection of the other four SUAs was based on a recent report of an intense social cognitive intervention in patients with treatment-resistant chronic pain 32 ; patients were included in this study if they reported (1) relational problems with their support partner, (2) stressors, and (3) distress, depression, or anxiety. Sub-groups of patients were obtained by selecting those who experienced all three factors [SUA6 and SUA8], and those having depressive or anxious symptoms [SUA5 and SUA7].…”
Section: Sub-group Analysesmentioning
confidence: 99%